P422 How achievable are the STRIDE-II treatment targets in real-world practise and do they affect outcome?. (21st January 2022) - Routledge, E; Meade, S; Sharma, E; Zeki, S; Ray, S; Anderson, S; Sanderson, J; Mawdsley, J; Samaan, M
Abstract: Background: The Selecting Therapeutic Targets in Inflammatory Bowel Disease (STRIDE) initiative provides recommendations on treatment targets for patients with Crohn's disease (CD). The Simple Endoscopic Score for CD (SES-CD) is a validated endoscopic score and STRIDE-II recommends its use in clinical practice. We aimed to assess whether the STRIDE-II endoscopic endpoints are achievable and whether the degree of mucosal healing (MH) affects long term outcomes. Methods: This is a retrospective observational study from, 2015–2020. We included patients with CD who had a baseline and follow-up SES-CD score after biologic therapy initiation. Data was collected via electronic records. The primary outcome was treatment failure, defined as the need for: i) change of biological therapy ii) corticosteroid use iii) CD-related hospitalisation or iv) surgery. We compared rates of treatment failure with the degree of MH achieved. Patients were followed up until treatment failure or study end (Aug, 2021). Statistics were performed using GraphPad v9.1.0 Software. Results: 50 patients were included (Fig, 1). Table, 1 shows the baseline characteristics. The median time to interval colonoscopy was, 16.3 (11.2–21.3) months. The proportion of patients achieving STRIDE-II end-points were: SES-CD (28, 56%), absence of ulcers (25, 50%) and endoscopic response [50% reduction in SES-CD] (31, 62%). Combined remission (SES-CD and Harvey Bradshaw Index [HBI] <5) occurred in, 25 cases (50%). Treatment failure occurred in, 13 (26%) patients: biologic switch (7/50, 14%), corticosteroids use (2/50, 4%), CD-related admission (5, 10%), or surgery (6, 12%). Median time to treatment failure was, 19 months. Fig, 2 shows the cumulative risk of treatment failure according to the achievement, or otherwise, of STRIDE-II endoscopic targets. Additionally, we show outcomes for combined endoscopic and clinical remission (HBI<5). Failure to achieve SES-CD or a, 50% improvement in SES-CD were the strongest predictors for treatment failure. Conclusion: In real-world clinical practice, calculating SES-CD scores at serial endoscopies is feasible and STRIDE-II targets are achievable in a reasonable proportion of patients (50%). Furthermore, achieving these targets has favourable long-term, clinically relevant outcomes.